2002
DOI: 10.1073/pnas.192464099
|View full text |Cite
|
Sign up to set email alerts
|

The Neandertal type site revisited: Interdisciplinary investigations of skeletal remains from the Neander Valley, Germany

Abstract: The 1856 discovery of the Neandertal type specimen (Neandertal 1) in western Germany marked the beginning of human paleontology and initiated the longest-standing debate in the discipline: the role of Neandertals in human evolutionary history. We report excavations of cave sediments that were removed from the Feldhofer caves in 1856. These deposits have yielded over 60 human skeletal fragments, along with a large series of Paleolithic artifacts and faunal material. Our analysis of this material represents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(101 citation statements)
references
References 31 publications
4
91
0
6
Order By: Relevance
“…The retrieval of putative Neanderthal mtDNA sequences (Krings et al 1997(Krings et al , 1999(Krings et al , 2000Ovchinnikov et al 2000;Schmitz et al 2002) is the major highlight in ancient human DNA studies because it allowed direct testing of hypotheses about the origin of the modern human gene pool. Importantly, recent suggestions that ancient sequences such as the Neanderthal results might be due to PCR artefacts (Pusch & Bachmann 2004) appear unjustified, and may result from poor experimental design and methodology (Serre et al 2004b).…”
Section: Ancient Human Dna: a Contentious Issuementioning
confidence: 99%
“…The retrieval of putative Neanderthal mtDNA sequences (Krings et al 1997(Krings et al , 1999(Krings et al , 2000Ovchinnikov et al 2000;Schmitz et al 2002) is the major highlight in ancient human DNA studies because it allowed direct testing of hypotheses about the origin of the modern human gene pool. Importantly, recent suggestions that ancient sequences such as the Neanderthal results might be due to PCR artefacts (Pusch & Bachmann 2004) appear unjustified, and may result from poor experimental design and methodology (Serre et al 2004b).…”
Section: Ancient Human Dna: a Contentious Issuementioning
confidence: 99%
“…Phylogenetic analysis showed that it falls outside the variation of contemporary humans and shares a common ancestor with mtDNAs of present-day humans approximately half a million years ago 5,6 . Subsequently, mtDNA sequences have been retrieved from eleven additional Neanderthal specimens: Feldhofer 2 in Germany 7 , Mezmaiskaya in Russia 8 , Vindija 75, 77 and 80 in Croatia 9,10 , Engis 2 in Belgium, La Chapelle-aux-Saints and Rochers de Villeneuve in France 10 , Scladina in Belgium 11 , Monte Lessini in Italy 12 , and El Sidron 441 in Spain 13 . Although some of these sequences are extremely short, they are all more closely related to one another than to modern human mtDNAs 9,11 .…”
mentioning
confidence: 99%
“…modern human remains has been assigned to either later phases of the Upper Paleolithic [Cro-Magnon (France), La Rochette (France), and Konȇprusy (Czech Republic) (10)(11)(12)] or the Holocene [Engis (Belgium), Hahnöfersand (Germany), St. Prokop (Czech Republic), Velika Pećina (Croatia), and Vogelherd (Germany) (13)(14)(15)(16)(17)(18)]. Direct and indirect dating has placed several Neandertal specimens at the beginning and the middle of this chronological period [Arcy-sur-Cure (Grotte du Renne, France), Feldhofer (Germany), Saint-Césaire (France), and Zaskalnaya (Ukraine) (19)(20)(21)(22)] and has placed others toward the more recent end in the cul-de-sac of Iberia [Cabezo Gordo (Spain), Columbeira (Portugal), Figueira Brava (Portugal), and Zafarraya (Spain) (23)(24)(25)]. Moreover, two Neandertals from Vindija Cave in Croatia yielded radiocarbon determinations at the end of this transitional period (15).…”
mentioning
confidence: 99%